Methodological Alternative for the Development of the Ability to Measure from the Physical Subject in the First Year Students of the Mathematical-Physical Career - Pozo, E.; Pérez, J. (Revista Cubana de Física, 2011)
The methodological alternative suggested develop the measurement skill on the first year student of mathematics and physics of the university of pedagogical science in Pinar del Río has his foundation on P. Ya. Galperin is theory for the formation of mental actions and on the theory of advanced education. This alternative helps improve the quality of learning teaching process since the methodological work up to the lesson and contribute to offer ways of professional actions to the future graduated as physics´ professor. The results obtained during the application can be accepted as an option to direct the process for developing skills and concepts.